2006
DOI: 10.1590/s0004-282x2006000500021
|View full text |Cite
|
Sign up to set email alerts
|

Estudio comparativo de las funciones ejecutivas entre pacientes con enfermedad de Parkinson y pacientes con enfermedad degenerativa cerebelosa

Abstract: RESUMEN -Objetivo:Comparar el rendimiento en tareas de función ejecutiva (FE) en sujetos con enfermedad de Parkinson (EP) leve a moderada (Hoehn y Yahr ≤3) no dementes y en sujetos con enfermedad degenerativa cerebelosa pura (EC), a fin de evaluar el eventual rol diferencial de los ganglios basales y el cerebelo en esa función. Método: Se evaluaron 14 pacientes con EP y 14 con EC apareados por sexo, educación, duración de enfermedad y MMSE, mediante tests neuropsicológicos estándar y el test de Wisconsin [WCST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
1
0
1
Order By: Relevance
“…Agreeing with this hypothesis statement, Abel et al 44 had found a higher number of perseverative errors in people with cerebellar lesions than to those with basal ganglia injuries. 44 In addition, Berman et al 45 found an activation of cerebellum when changing criteria during the WSCT, 45 demonstrating the link between mental infl exibility and cerebellum injuries. Some limitations should be considered, as the low number of participants assessed.…”
Section: Discussionmentioning
confidence: 91%
“…Agreeing with this hypothesis statement, Abel et al 44 had found a higher number of perseverative errors in people with cerebellar lesions than to those with basal ganglia injuries. 44 In addition, Berman et al 45 found an activation of cerebellum when changing criteria during the WSCT, 45 demonstrating the link between mental infl exibility and cerebellum injuries. Some limitations should be considered, as the low number of participants assessed.…”
Section: Discussionmentioning
confidence: 91%
“…As "funções executivas", no entanto, não constituem matéria simples de definição, existindo na literatura diferentes modelos teóricos para explicá-las. Abel et al (2006) colocam que este foi um termo descrito por Luria 3 e trabalhado por Lesak , o qual corresponderia a complexos processos cognitivos, dentre os quais se incluiria a formação de estratégias, a antecipação, a escolha e a aplicação de um planejamento de ações adequadas a determinadas metas, além da capacidade de manter uma estratégia, no caso da mesma ser apropriada, ou de mudá-la, quando a mesma deixa de obter êxito. No mesmo sentido, Souza et al (2001) afirmam que as "funções executivas" podem compreender flexibilidade, aquisição de hábitos e habilidades e planejamento.…”
unclassified